Risk of low birthweight associated with the timing and frequency of antenatal care visits in Lao PDR: a retrospective cohort study - Shiori Nagatani; Sayaka Horiuchi; Kenzo Takahashi; Masaaki Matsuura; Kongsit Ounchit; Kazue Yamaoka (BMC, 2023)
Abstract Background Antenatal care (ANC) plays an important role in preventing low birthweight (LBW). Whereas the government of Lao People's Democratic Republic (Lao PDR) has committed to increasing the usage of ANC, little attention has been given to the early initiation of ANC. The present study assessed the influence of delayed and fewer ANC visits on LBW in the country. Methods This is a retrospective cohort study conducted at Salavan Provincial Hospital. Study participants were all pregnant women who gave birth at the hospital between 1 August 2016 and 31 July 31 2017. Data were collected from medical records. Logistic regression analyses were performed to quantify the relationship between ANC visits and LBW. We also investigated factors associated with inadequate ANC visits: first ANC visit after the first trimester or < 4 ANC visits. Results The mean birth weight was 2808.7 g [standard deviation: SD 455.6]. Among 1804 participants, 350 (19.4%) had babies with LBW, and 147 (8.2%) had inadequate ANC visits. In multivariate analyses, compared to participants with adequate ANC visits, those with ≥ 4 ANC visits and the first ANC visit after the second trimester, those with < 4 ANC visits, and those with no ANC visits had higher odds ratios (ORs) of LBW: 3.77 (95% confidence interval: CI = 1.66-8.57), 2.39 (95% CI = 1.18-4.83) and 2.22 (95% CI = 1.08-4.56), respectively. Younger maternal age (OR 1.42; 95% CI = 1.07-1.89), government subsidisation (OR 2.69; 95% CI = 1.97-3.68) and ethnic minority (OR 1.88; 95% CI = 1.50-2.34) were associated with increased risk of insufficient number of ANC visits after adjusting for covariates. Conclusions Frequent and early initiation of ANC was associated with a reduction in LBW in Lao PDR. Encouraging childbearing-aged women to receive sufficient ANC at proper timing may lead to a reduction in LBW and improvement in short- and long-term health outcomes of neonates. Special attention will be needed for ethnic minorities and women in lower socioeconomic classes.